Eclipta prostrata (L.) L.: Traditional Use, Phytochemistry, and Pharmacology - Sanyal, R.; Nandi, S.; Mandal, S.; Dewanjee, S.; Al-Tawaha, A.R.; Bursal, Ercan; Biswas, P. (Springer Nature, 2022)
Herbs had been exploited by different cultures throughout history. In public wellness programs of the countries, drugs of natural origin play a crucial role. Eclipta prostrata (L.) L. also known by the name of Eclipta alba (L.) Hassk is generally called bhringraj in Indian traditional medicine and false daisy in English. It is a common folk medicinal plant falling under the family Asteraceae. It is an annual, herbaceous, small, branched plant occurring mainly in the tropical and subtropical areas. The plant performs a historic contribution in the pharmaceuticals and has a reassuring cosmetic application in addition to therapeutic applications. The plant possesses a number of bioactive compounds including coumestans, flavonoids, volatile oils, terpenoids and their glycosides, steroids, polyacetylenes, and polypeptides, etc. which are responsible for some of the important pharmacological activities including antimicrobial, analgesic, anti-nociceptive, anti-inflammatory, hepatoprotective, antiviral, immunomodulatory activity, etc. In ayurveda, the extract of the leaf is contemplated as a rejuvenative especially for black hairs and a potential tonic for liver. Several researchers evaluated the acute toxicity of the plant concluding that the LD50 (Lethal dose 50) of E. prostrata was more than 2.0 g/kg in mice and rats, hence considered a moderately safe drug. This book chapter highlights the information on taxonomic description, photochemical constituents, traditional and folk uses, pharmacology and safety, and toxicity of E. prostrata in an aim to furnish recommendations for future research and possibilities for a good application of the herb. Particular attention is given to hepatoprotective, antidiabetic effect, hair growth and alopecia, analgesic, anti-inflammatory, antioxidant, antimicrobial, immunomodulatory, anticancer, and antitumor effects of the plant so that the possible utilization of the plant can be evaluated in pharmaceutics as well as in agricultural resource. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.
Keywords: Bhringraj; Coumestans; Eclipta Prostrata (L.) L.; Pharmacological Activities; Safety And Toxicity; Traditional Use